Exploring multiple ontologies of drought in agro‐pastoral regions of Northern Tanzania: a topological approach. Issue 1 (24th July 2015) - Goldman, Mara J; Daly, Meaghan; Lovell, Eric J
Abstract : There has been increased focus within the human dimensions of climate change on understanding the complex and multiple ways of 'knowing' climate. While these discussions are important in recognising different ways of knowing the climate and climate change processes already underway, we argue that this epistemological approach is limited and challenging. It begins with an assumption that there is one world (climate) out there that can just be known differently, and that knowledge can be isolated from ways of being and acting in the world. This often results in a distilling of complex knowledge practices into information for the purposes of integration. Drawing from a material‐semiotic approach from Science and Technology Studies (STS), we propose a shift of focus to ontology, with an emphasis on the enactment of knowledge and reality (climate) simultaneously. We present ethnographic data from two drought events (2008/2009 and 2010/2011) among Maasai pastoralists in Northern Tanzania in East Africa to illustrate the value of such an approach, using multiple topologies (regional, network, fluid) for thinking through and following multiple enactments of drought in practice.